An Analysis of Factors Influencing Parents in the Selection of Schools - Ahmad Faizuddin; Tumin An-Nuaimy; Muhammad Irzal (Faculty of Educational Sciences, Syarif Hidayatullah State Islamic University, 2016)
Abstract Sekolah Indonesia Kuala Lumpur (SIKL), as an International school provided by the government of Indonesia is not a favourite among Indonesian parents living in Malaysia. They prefer to send their children to other International or Islamic-based schools. It results in a big question on what are their reasons behind such decision. Thus, the aim of this study is to explore the experiences of Indonesian parents living in Kuala Lumpur, Malaysia, regarding their reasons of not choosing Indonesian School for their children. For the purpose of this research, a case study approach was adopted. Using in-depth interviews, three Indonesian parents who live in Malaysia and opt for other International schools were selected. The data of the interviews were analysed and categorized based on unique themes. The result of an interpretive analysis found that parents’ reasons are demonstrated in three interrelated themes: (1) The need of specific curriculum, (2) The lack of creative teaching methods used in Indonesian School, and (3) The less strategic location of Indonesian School. As a final point, this paper provides an insight analysis of parents’ reasons and some recommendations for improvement. Abstrak Sekolah Indonesia Kuala Lumpur (SIKL), sebagai sekolah Internasional yang disediakan oleh pemerintah Indonesia, tidaklah favorit di antara orang tua Indonesia yang tinggal di Malaysia. Mereka lebih memilih untuk mengirimkan anak-anak mereka ke sekolah Internasional lain atau sekolah Islam. Hal ini membuat pertanyaan besar kepada apa alasan mereka di balik keputusan tersebut. Penelitian ini bertujuan untuk menyelidiki pengalaman orang tua Indonesia yang tinggal di Kuala Lumpur, Malaysia, terkait dengan alasan mereka tidak memilih sekolah Indonesia bagi anak-anak mereka. Untuk tujuan penelitian ini, pendekatan studi kasus dilakukan. Menggunakan wawancara mendalam, tiga orang tua Indonesia yang tinggal di Malaysia dan memilih sekolah internasional lain dipilih. Data wawancara dianalisis dan dikelompokkan berdasarkan tema-tema khusus. Hasil interpretasi analisis menemukan bahwa alasan orang tua tergambarkan pada tiga item: (1) kebutuhan kurikulum tertentu, (2) kurangnya metode mengajar kreatif yang digunakan di sekolah Indonesia, dan (3) kurang strategis dari lokasi sekolah Indonesia. Akhirnya, tulisan ini memberikan analisis wawasan tentang alasan orang tua dan rekomendasi untuk peningkatan. How to Cite : Faizuddin, A. An-Nuaimy, T. Irzal, M. (2016). An Analysis of Factors Influencing Parents in the Selection of Schools. TARBIYA: Journal Of Education In Muslim Society, 3(1), 90-95. doi:10.15408/tjems.v3i1. 3398. Permalink/DOI: http://dx.doi.org/10.15408/tjems.v3i1.3398